Expression of type 8 capsular polysaccharide and production of toxic shock syndrome toxin 1 are associated among vaginal isolates of Staphylococcus aureus. - Lee, J C (1990)
A colony immunoblot method was developed for serotyping the capsular polysaccharides expressed by Staphylococcus aureus isolates. The method was rapid and specific and was performed with either polyclonal or monoclonal antibodies specific for each of the capsule types. S. aureus isolates were obtained from patients with toxic shock syndrome (TSS) or other staphylococcal infections and from asymptomatic women with vaginal colonization. Among the vaginal isolates of S. aureus, expression of the type 8 capsule was significantly (P less than 0.001) more frequent among strains that produced TSS toxin 1 (TSST-1) than it was among TSST-1-negative strains. In contrast, the frequency of type 8 capsule expression was similar among both TSST-1-positive and -negative strains of S. aureus from patients with nonvaginal TSS. When all vaginal and nonvaginal isolates were compared, TSST-1-negative S. aureus strains were equally distributed among the type 5 and 8 and nontypeable capsule groups, whereas TSST-1-positive strains were predominantly capsule type 8.